2019
DOI: 10.3390/lubricants7070061
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Pivot Stiffness on the Performances of Five-Pad Tilting Pad Bearings

Abstract: The role of the pivot flexibility in tilting-pad journal bearings (TPJBs) has become essential, particularly for bearings working at high applied load and relatively high rotor speeds. Predictions from a simple bearing model with rigid pivots show incorrect estimation of the dynamic coefficients in comparison with the experimental results. Normally, the more flexible the pad pivot, the lower the dynamic coefficients because the stiffness of the pivot takes in series with the stiffness and damping of the oil fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…The TEHD model of TPJBs was developed and validated by experimental data in [28] and was improved for the elastic pivot stiffness and thermal feature, as partially done in [29] for two-axial groove journal bearings. Figure 1 shows the scheme of a pad-shaft system in a rocker-backed TPJB, where O b and O j are the center of the bearing and the shaft, respectively.…”
Section: Bearing Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…The TEHD model of TPJBs was developed and validated by experimental data in [28] and was improved for the elastic pivot stiffness and thermal feature, as partially done in [29] for two-axial groove journal bearings. Figure 1 shows the scheme of a pad-shaft system in a rocker-backed TPJB, where O b and O j are the center of the bearing and the shaft, respectively.…”
Section: Bearing Modelingmentioning
confidence: 99%
“…It was found that the effect of the flexibility of the pivot along the η direction in the prediction of the performances of TPJBs is very important. The pivot stiffness estimated from the Hertz contact theory is always higher than that obtained by experiments, especially for rocker-backed bearings [29]. In order to improve the numerical simulation, the pivot stiffness estimated by experiment is introduced to the code.…”
Section: Bearing Modelingmentioning
confidence: 99%
See 3 more Smart Citations